Antituberculosis Activity of Parang Romang (Boehmeria virgata (Forst.) Guill) Stem Extract - Muhammad Rusdi; Muhammad Ikhlas; Nur Pratiwi Kartikasari (Universitas Islam Negeri Alauddin Makassar, 2021)
Parang Romang (Boehmeria virgata (Forst.) Guill) is one of the plants empirically used by the people of South Sulawesi. This study aimed to test the activity of Parang Romang Extract against Mycobacterium tuberculosis. The 96% ethanol extract obtained was fractionated by the liquid-solid extraction method: obtained n-Hexan soluble extract and n-Hexan insoluble extract. Samples of 96% ethanol extract, soluble extract of n-Hexan and insoluble extract of n-Hexan were made in series of concentrations of about 25, 50, 75, and 100 µg/ml. The inhibition test of Mycobacterium tuberculosis used the MODS method on the Mycobacterium tuberculosis strain H37RV. Color reagents then identify extracts that provide inhibition. The results of the minimum inhibition concentration of Mycobacterium tuberculosis showed that a 100 µg/ml of n-Hexan soluble extract was able to inhibit the growth of Mycobacterium tuberculosis strain H37RV.